American Time Use Survey (ATUS), 2004 ([Verlag nicht ermittelbar], 2006)
The American Time Use Survey (ATUS) collects information on how people living in the United States spend their time. Estimates show the kinds of activities people engage in and the time they spend involved in these activities by age, sex, educational attainment, labor force status, and other characteristics, as well as by weekday and weekend day. Data about the quality of life in the United States include how much time people spend working, sleeping, caring for children, volunteering, participating in religious activities, commuting, or relaxing, as well as with whom they spend their time. The ATUS sample is drawn from households that have completed their final month of interviews for the Current Population Survey, the federal survey that is the source of the nation's unemployment rate.